2007
DOI: 10.1016/j.mcn.2007.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a novel phosphorylation site on the GluR1 subunit of AMPA receptors

Abstract: Phosphorylation of various AMPA receptor subunits can alter synaptic transmission and plasticity at excitatory glutamatergic synapses in the central nervous system. Here, we identified threonine-840 (T840) on the GluR1 subunit of AMPA receptors as a novel phosphorylation site. T840 is phosphorylated by protein kinase C (PKC) in vitro, and is a highly turned-over phosphorylation site in the hippocampus. Interestingly, the high basal phosphorylation of T840 in the hippocampus is maintained by a persistent activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 35 publications
6
55
0
Order By: Relevance
“…In our Phos-tag experiments we are able to detect single phosphorylated S845 or S831 species, as well as a more complex population-containing multiple phosphorylations. GluA1 is also known to be phosphorylated at S567 by CaMKII (38), S818 and T840 by PKC (39,40), and more recently at S863 by PAK3 (41). Interestingly, we recently showed that stimulation of neurons with the neuropeptide PACAP38 resulted in coordinated increases in phosphorylation of GluA1 S845 and dephosphorylation of T840 (42), indicating a complex relationship exists between different phosphorylation sites.…”
Section: Discussionmentioning
confidence: 99%
“…In our Phos-tag experiments we are able to detect single phosphorylated S845 or S831 species, as well as a more complex population-containing multiple phosphorylations. GluA1 is also known to be phosphorylated at S567 by CaMKII (38), S818 and T840 by PKC (39,40), and more recently at S863 by PAK3 (41). Interestingly, we recently showed that stimulation of neurons with the neuropeptide PACAP38 resulted in coordinated increases in phosphorylation of GluA1 S845 and dephosphorylation of T840 (42), indicating a complex relationship exists between different phosphorylation sites.…”
Section: Discussionmentioning
confidence: 99%
“…Although our data from the S845A mutants are the same as those observed in the GluR1 "double phosphomutants" , it is slightly different from the "penta phosphomutants," which showed LTD deficits only in the adults ). Unlike the "double" or the "single" phosphomutants, the "penta" phosphomutants carry additional three mutations at amino acid residues, including a novel phosphorylation site, T840 (Delgado et al 2007;Lee H-K et al 2007). The lack of T840 apparently rescued the LTD phenotype in juveniles lacking both S831 and S845.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of the two membrane-proximal PKC sites (SRS 816 ES 818 KR) enhances interaction between the actin-binding 4.1N protein and the GluA1 C-terminal domain, which facilitates insertion of this subunit into the plasma membrane (Boehm et al, 2006;Lin et al, 2009), a mechanism involved in long-term potentiation. Phosphorylation of TST 840 LPR by PKC has been suggested to influence synaptic transmission in an age-dependent fashion (Lee et al, 2007b). Two other GluA1 phosphorylation sites control functional properties of AMPA receptor channels.…”
Section: Acid and Kainate Receptor Phosphorylationmentioning
confidence: 99%